Early career researchers and their publishing and authorship practices. Issue 3 (29th March 2017) - Nicholas, David; Rodríguez‐Bravo, Blanca; Watkinson, Anthony; Boukacem‐Zeghmouri, Cherifa; Herman, Eti; Xu, Jie; Abrizah, Abdullah; Świgoń, Marzena
Abstract : This study presents findings from the first year of the Harbingers research project, a 3‐year longitudinal study of early career researchers (ECRs), which sought to ascertain current and changing habits in scholarly communication. The study recruited 116 science and social science ECRs from seven countries who were subject to in‐depth interviews, and this paper reports on findings regarding publishing and authorship practices and attitudes. A major objective was to determine whether ECRs are taking the myriad opportunities proffered by new digital innovations, developing within the context of open science, open access, and social media, to publish their research. The main finding is that these opportunities are generally not taken because ECRs are constrained by convention and the precarious employment environment they inhabit and know what is best for them, which is to publish (in high impact factor journals) or perish.